Narrative Review: Social and Cultural Determinants of Chronic Energy Deficiency among Women in Developing Countries - Fitri Handayani (CV. Devitara, 2025)
Chronic Energy Deficiency (CED) among women remains a major nutritional problem in developing countries and has significant impacts on maternal health, pregnancy outcomes, and future generations. The high prevalence of CED indicates that this issue is not solely related to inadequate nutrient intake, but is also influenced by structural social and cultural determinants that interact with one another. This article aims to examine the role of social and cultural determinants in the occurrence of CED among women in developing countries. This article was developed using a narrative review approach based on open-access journal articles, official reports from the World Health Organization (WHO) and UNICEF, as well as population-based and qualitative studies published between 2016 and 2025. The keywords used included chronic energy deficiency, women, social determinants, and cultural factors. Relevant articles were selected based on topic relevance, developing country context, and a focus on women, and were then thematically analyzed to identify recurring patterns of social and cultural determinants. The findings indicate that poverty, low levels of education, limited access to nutritious food, gender inequality, and women’s workload significantly contribute to the occurrence of CED. In addition, cultural norms and practices related to intra-household food distribution and specific food taboos further exacerbate women’s vulnerability to CED, particularly during the reproductive age. Chronic Energy Deficiency among women is a structural problem that requires nutrition interventions sensitive to social and cultural contexts as well as gender equity in order to achieve sustainable improvements in nutritional status.